Green Turtle (Chelonia mydas) Nesting Underscores the Importance of Protected Areas in the Northwestern Gulf of Mexico - Shaver, Donna J.; Frandsen, Hilary R.; George, Jeffrey A.; Gredzens, Christian (Frontiers in Marine Science, 2020)
Knowledge of the spatial and temporal distribution of green sea turtle (Chelonia mydas) nesting is crucial for management of this species. Limited data exist on the nesting patterns of green turtles along the northwestern Gulf of Mexico (GOM) coast. From 1987 to 2019, 211 green turtle nesting activities were documented on the Texas coast, including 111 confirmed nests and 100 non-nesting emergences. Of the 111 nests, 99 were located on North Padre Island (97 at Padre Island National Seashore (PAIS), 2 north of PAIS) and 12 on South Padre Island (6 within the Laguna Atascosa or Lower Rio Grande Valley National Wildlife Refuges (NWR), 6 outside of a NWR). Of the 100 non-nesting emergences, 75 were on North Padre Island (70 at PAIS, 5 north of PAIS), 21 on South Padre Island (9 within a NWR, 12 outside of a NWR), 1 on Boca Chica Beach, 2 on San Jose Island, and 1 on Mustang Island. Nearly all of the nests (92.8%) and most of the non-nesting emergences (79.0%) were on property protected by the U.S. Department of the Interior as PAIS or a NWR, and confirmed nest density was largest at PAIS, highlighting the importance of these federally protected lands as nesting habitat for this threatened species. Of the 111 located nests, 8 were predated. Mean hatching success of the 103 non-predated nests was 77.4%, and 9,475 hatchlings were released from the predated and non-predated nests. The largest annual number of green turtle nests documented was 29 in 2017. Nesting appeared to increase since 2010, but at a much lower rate than at other GOM nesting beaches. To aid with recovery, efforts should be undertaken to monitor long-term nesting trends, protect nesting turtles and nests, and investigate potential causes for the slower recovery in Texas. Additionally, the genetic structure of the population that nests in Texas should be determined to reveal if the population warrants recognition as a unique management unit, or if it is part of a broader unit that is a shared nesting resource with Mexico which is already being considered as a unique management unit.